Предмет: Алгебра,
автор: lty99
при m=-0,2 4m(3+5m)-(m+1)(m-2)
Ответы
Автор ответа:
0
Подставим значение m=-0,2 в уравнение
4*(-0,2)*(3+5*(-0,2))-(-0,2+1)(-0,2-2)=
=-0,8*(3-1)-(0,8)*(-2,2)=
=-1,6+1,76=
= 0,16
Автор ответа:
0
Если m=-0,2,то 4*(-0,2)*(3+5*(-0,2))-(-0,2+1)*(-0,2-2)=-0,8*2-0,8*(-2,2)=-1,6-1,76=-3,36
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: manicevartur
Предмет: Английский язык,
автор: Padenkova1234
Предмет: Математика,
автор: Андрей25
Предмет: Математика,
автор: girl111